Фонетическaя природa ротaцизмa в чувaшском языке - Кортaбaевa, Г. К. (Journal of Oriental Studies, 2018)
The Turkic languages have long been found very interesting is the phonetic phenomenon of rhotacism. Nature phonetic matching r ~ z is one of the most mysterious phenomena in Turkic studies. Phonetic phenomenon rhotacism still remains a controversial issue in linguistics. In this article the author comments on a number of different hypotheses and tries to uncover its meaning.